Performance and stability of BaCe0.8−xZr0.2InxO3−δ-based materials and reversible solid oxide cells working at intermediate temperature. (23rd November 2017) - Yang, Shaojing; Wen, Yabing; Zhang, Sanpei; Gu, Sui; Wen, Zhaoyin; Ye, Xiaofeng
Abstract: Proton-conducting reversible solid oxide cells (PC-RSOCs) have attracted much attention for their advantages of working as energy storage devices. In this study, orthorhombic-perovskite structure BaCe0.8−x Zr0.2 Inx O3−δ (x = 0, 0.1, 0.2, 0.3, 0.4) materials have been synthesized. The effect of different indium doping contents on the stability and electrical properties has been investigated. Experimental results reveal that the BaCe0.5 Zr0.2 In0.3 O3−δ possesses the highest proton conductivity with desirable density. Besides, the stability of BaCe0.5 Zr0.2 In0.3 O3−δ is obviously improved in moist air (20 vol% H2 O) atmosphere. Anode-supported PC-RSOC with BaCe0.5 Zr0.2 In0.3 O3−δ membrane as an electrolyte displays a maximum power density of 151 mW·cm −2 at 700 °C in solid oxide fuel cell (SOFC) mode. Meanwhile, the PC-RSOC with BaCe0.5 Zr0.2 In0.3 O3−δ electrolyte membrane in solid oxide electrolysis cell (SOEC) mode can also manifest high current density of −729 mA cm −2 at 700 °C with an applied voltage of 1.5 V, and maintains a stable current density of around −124 mA·cm −2 at 700 °C with an applied voltage of 1.1 V for more than 60 h. These encouraging results suggest the potential application of BaCe0.5 Zr0.2 In0.3 O3−δ as electrolyte material for intermediate-temperature PC-RSOCs. Highlights: The properties of In-doped BaCe0.8−x Zr0.2 Inx O3−δ were systematically studied. The BaCe0.5 Zr0.2 In0.3 O3−δ (BCZI3) ceramic displayed high conductivity and density. The BCZI3 presented excellent stability in moist air (20 vol%) atmosphere. The RSOC with BCZI3 electrolyte showed good performance and stability.